Seasonal Variation of the Burden of Atopic Dermatitis in Finnish Primary Care: A Database Study on Effects of Weather and Air Quality - Emilia Räisänen; Anita Remitz; Alexander Salava (Acta Dermato-Venereologica)
The burden of atopic dermatitis has been increasing in Finland during recent decades and seems to vary seasonally. The aim was to investigate the effect of season and weather factors on patient numbers of primary care. Data bank information of the Finnish Institute for Health and Welfare was analysed for frequency of atopic dermatitis patients in the primary care of Helsinki during 2018–2023. In addition, the seasonal burden was compared with weather data from the Finnish Meteorological Institute. Patient numbers varied significantly during the year (p = 0.028). There was a recurrent seasonal variation with most atopic dermatitis diagnoses in January, February, March, and November and the least in July and August. A significant inverse association was observed between atopic dermatitis patients and outside temperature (p = 0.004) and UV Index (p = 0.008). Low air quality was associated with a higher burden in primary care (p = 0.013). There was no significant association regarding rain (p = 0.103) or relative air humidity (p = 0.392). The burden of atopic dermatitis in primary care shows a significant seasonal variation. There are specific weather parameters that follow similar patterns and likely comprise important extrinsic pathogenetic factors. It is reasonable to address the changing burden of atopic dermatitis with seasonally directed medical measures, education, and resources.